A Technical Note on the Seventh Plan of India 1985-90 - Planning Commission (Planning Commission Government of India, 1986)
This study synthesizes a series of technical documents underpinning India’s Seventh Five Year Plan (1985–1990), focusing on macroeconomic modeling, sectoral interlinkages, and financial resource mobilization. The planning framework integrates a core model with multiple sub-models covering demography, employment, poverty, agriculture, industry, financial resources, and external trade to guide strategic resource allocation and growth targets. Emphasis is placed on food security, employment generation, productivity enhancement, and poverty reduction, particularly through agricultural expansion in high-poverty regions and infrastructure-led industrial development. The analysis highlights the pivotal role of household savings as the primary net source of domestic finance, supporting both government expenditure and private corporate investment through structured financial intermediation. Detailed projections of private corporate savings, public and private sector investments, and inter-sectoral borrowing illustrate the mechanics of resource mobilization during the Plan period. Input-output and import-use coefficient analyses for 1984–85 and 1989–90 further reveal sectoral dependencies, especially on energy imports such as crude petroleum, alongside relative self-sufficiency in core agricultural commodities. Overall, the documents provide a comprehensive empirical foundation for understanding India’s planned economic transition during the late 1980s, demonstrating how integrated economic modeling, financial planning, and sectoral analysis were employed to pursue sustainable growth, fiscal stability, and equitable development.
Government of India Planning Commission
Keywords: Seventh Five Year Plan; Economic Modeling; Sectoral Input-Output Analysis; Agricultural Productivity; Poverty Alleviation; Employment Generation; Financial Resource Mobilization; Household Savings; Private Corporate Sector; Industrial Development; Import Dependency; Trade and Tax Structure